Implementation of the Morning TPQ Program in the Development of Early Childhood Religious Values (A Case Study at TPQ Al-Huda Jondang, Jepara) - Husnun Nadiyya; Ana Rahmawati (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the learning strategies implemented in the TPQ Morning Program at TPQ Al-Huda Jondang in developing the religious values of early childhood. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that the learning strategies include auditory habituation through listen-and-repeat methods, a combination of classical and individual approaches, the use of concrete media, game-based learning, and gradual habituation of worship practices. These strategies are integratively applied to support the internalization of religious values, covering cognitive aspects, worship practices, and daily behavior. In addition, the implementation of the program in the morning supports children’s learning readiness due to more optimal physical and mental conditions. In conclusion, adaptive, varied, and habituation-based learning strategies play an important role in developing religious values in early childhood holistically. The integration of multiple learning strategies becomes a key factor in enhancing the effectiveness of religious value internalization within non-formal Islamic education contexts.